The Post-millennial British Novel - Nagy-Seres, Imola (Hungarian Journal of English and American Studies, 2020)
Book review: Bentley, Nick, Nick Hubble, and Leigh Wilson, eds. The 2000s: A Decade of Contemporary British Fiction. The Decades Series 4. London: Bloomsbury Academic, 2015. 297 pages. ISBN 9781441112156. Pbk. £85.